2022
DOI: 10.3390/pr10051025
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Chromatography and Fractionation of Proteins from Whey—A Review

Abstract: Membrane chromatography (MC) is an emerging bioseparation technology combining the principles of membrane filtration and chromatography. In this process, one type of molecule is adsorbed in the stationary phase, whereas the other type of molecule is passed through the membrane pores without affecting the adsorbed molecule. In subsequent the step, the adsorbed molecule is recovered by an elution buffer with a unique ionic strength and pH. Functionalized microfiltration membranes are usually used in radial flow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…On the other hand, the 0.45 and 0.2 μm pore membranes gave rise to a prominent shift of signals from the OZ to the IZ, as the ring was suppressed, for the (+)­Target samples. The reason that ring suppression occurred more significantly for the membranes with smaller pore sizes is because these substrates exhibit higher hydrophobicity, leading to slower diffusion . In addition, to observe the iFluor-RFA on the membrane according to the target nucleic acid, the surface of the 0.2 μm CN membrane of the iFluor-RFA sample was observed by scanning electron microscopy (SEM) (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the 0.45 and 0.2 μm pore membranes gave rise to a prominent shift of signals from the OZ to the IZ, as the ring was suppressed, for the (+)­Target samples. The reason that ring suppression occurred more significantly for the membranes with smaller pore sizes is because these substrates exhibit higher hydrophobicity, leading to slower diffusion . In addition, to observe the iFluor-RFA on the membrane according to the target nucleic acid, the surface of the 0.2 μm CN membrane of the iFluor-RFA sample was observed by scanning electron microscopy (SEM) (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The reason that ring suppression occurred more significantly for the membranes with smaller pore sizes is because these substrates exhibit higher hydrophobicity, leading to slower diffusion. 39 In addition, to observe the iFluor-RFA on the membrane according to the target nucleic acid, the surface of the 0.2 μm CN membrane of the iFluor-RFA sample was observed by scanning electron microscopy (SEM) (Figure S5). In samples without target DNA, accumulation of RCA products was observed only in the OZ, whereas in samples with target DNA, more accumulation was observed in the IZ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Membrane adsorbers (MA) are thin, micro-or macro-porous layers that are functionalized with similar ligands to those used for resin-based chromatography [177], enabling them to preserve comparable resolution in separating molecules [178][179][180]. Numerous studies have reported that ion exchange membrane adsorbers can be used to fractionate proteins from whey, but limited information is available regarding the use of affinity membrane adsorbers for whey protein separation due to the highly expensive nature of affinity chromatography [181]. The fractionation of whey proteins using such ion exchange membrane adsorbers consists of two main steps in a similar manner to resin bed chromatography, namely, anion exchange followed by cation exchange.…”
Section: Membrane Adsorber/membrane Chromatographymentioning
confidence: 99%
“…Small-molecular-weight bioactive peptides generated using EPH have great potential as health-promoting ingredients in the form of functional foods and nutraceuticals [3]. Beyond their role as sources of nutrients, such peptides have been shown to have a wide range of biological functions, including blood glucose regulation, and antihypertensive and cholesterol-lowering effects [4,5]. In the production of such bioactive peptides for human consumption, downstream separation technologies are essential unit operations implemented to improve vital sensory attributes as well as to concentrate bioactive constituents [6].…”
Section: Introductionmentioning
confidence: 99%